Internal Resource Optimization Challenges under the Public Service Agency (BLU) Framework: A Qualitative Institutional Study at Politeknik Negeri Semarang - Fariham Masula; Budi Eko Soetjipto; Agung Winarno (Jurnal Penelitian IPTEKS, 2026)
Vocational higher education institutions face growing pressure to balance academic duties with entrepreneurial demands. At Politeknik Negeri Semarang (Polines), several issues hinder the effective use of internal resources for business unit development. These include limited managerial flexibility under the Public Service Agency (BLU) scheme, gaps between institutional policies and on-ground practices, underused productive assets, slow adoption of entrepreneurial values, and fragmented internal–external collaboration. This study aims to identify the key obstacles that affect efforts to optimize internal resources in supporting entrepreneurial activities within Polines’ business units. Using a qualitative case study design, data were collected through interviews, observations, and document analysis, then processed in NVivo 15 using systematic coding. The findings show that challenges concentrate on three areas: managing productive assets, strengthening entrepreneurial practices, and improving collaborative networks. The study contributes theoretically by clarifying how institutional constraints shape resource optimization in vocational institutions, supporting insights from Institutional Theory and the Triple Helix Model. Practically, the study highlights the need for more adaptive asset governance, clear incentive mechanisms, and structured partnerships to enhance performance and sustain institutional development.